Aging with physical disabilities: experience intersected by stigma, social isolation and finitude - José Alves Martins; Miriam Aparecida Barbosa Merighi; Maria Cristina Pinto de Jesus; Helena Akemi Wada Watanabe (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To understand the experience from a perspective of elderly people with physical disabilities. Method: Qualitative study that interviewed 15 people from the Mato Grosso Association of Disabled Person. Testimonies were obtained from 2016 July to 2017 June in the metropolitan region of Cuiabá/Brazil. Data were organized in thematic categories and analyzed through social phenomenology of Alfred Schütz. Results: It was evidenced that the stigma intersects the experience of the physical deficiency including in the old age. The perpetuation of stigma translated into impaired identity, social isolation, lack of perspective and acceptance of finitude as inevitable, contributing to a negative experience in old age. Conclusion and implications for practice: The experience of aging with physical disability has an intrinsically multidimensional nature, confronting complex lives and social contexts hostile to the body diversity, which need to be considered in public policies, by service managers and professionals involved in the processes of care for the elderly with physical disability.